THE ROLE OF GEO-ENVIRONMENTAL VARIABLES IN UNDERSTANDING CAUSAL CO-FACTORS OF DISEASES OF UNKNOWN AETIOLOGY AND OTHER ENIGMATIC DISEASES IN AFRICA: A NARRATIVE REVIEW. - Vambe, Mcmaster; Coopoosamy , Roger; Kuben, Naidoo; Theophilus, Davies (Student's Journal of Health Research Africa, 2024)
Idiopathic diseases (ID) or diseases of unknown aetiology (DUA) are poorly understood diseases. These diseases are widespread in Africa and other regions of the world. In Africa, we also experience occasional outbreaks in a population, or a cluster of diseases appears for which the causes are unclear. Until now, there has been a lack of literature linking geo-environmental variables with DUA, perhaps due to under- and misdiagnosis of these diseases. However, some of the few existing reports have implicated geo-environmental variables as inducers of a wide spectrum of pathophysiological responses including apoptosis, fibrosis, inflammation, molecular damage, and oxidative tissue injuries. The present review therefore seeks to explore the critical role that these variables may play as co-factors or risk factors in the incidence and progression of a range of DUA in Africa. A comprehensive online search of journal databases (Google Scholar, ScienceDirect, PubMed, Scopus, and SpringerLink) was mounted to obtain requisite data that would enable tangible deductions to be drawn on the extent to which geo-environmental variables act as co-factors or risk factors in unraveling the mysteries of unknown aetiology; and to demonstrate the importance of including the geo-environmental component in a multi-factor explanation of the disease causative web. The databases were used to obtain reports related to DUA, disease clusters, and geo-environmental variables as disease risk factors in Africa. Findings from the present study help us understand and interpret unexpected DUA aetiological data, which are prerequisites for developing accurate and effective diagnosis, prevention, and improved management strategies for these diseases. It became clear from the present study that for us to fully understand the pathogenesis and progression of DUA, healthcare professionals investigating disease clusters should, perhaps team up with Medical Geologists, a research collaboration that rarely exists in most developing countries today.